Prevalence of Depressive Disorder among Patients with Epilepsy: a cross-sectional study - Devkota, Anup; Ghimire, Sapana; Thapa, Sheela (Journal of Karnali Academy of Health Sciences, 2021)
Background: Epilepsy is the most common neurological disease in the general population. Depression when comorbid in individuals with epilepsy contributes to low quality of life. As the epilepsy clinics do not routinely assess for major depression substantial opportunity exists to improve the quality of care for many people with epilepsy. The objective of the study was to study the prevalence of depressive disorder and associated factors in individuals with epilepsy.Methods: A cross-sectional study was conducted at the teaching hospital of Karnali Academy of Health Sciences, Jumla. Sixty patients with epilepsy meeting the inclusion criteria of the study were enrolled in the study. Data was collected using Patient Health Questionnaire-9 (PHQ-9) via face-to-face interview. Descriptive statistics was presented as frequency and percentages. Association between variables was assessed with Chi-square test. P-value of